Interferon-β modulates microglial polarization to ameliorate delayed tPA-exacerbated brain injury in ischemic stroke - Kuo, Ping-Chang; Weng, Wen-Tsan; Scofield, Barbara A.; Paraiso, Hallel C.; Bojrab, Paul; Kimes, Brandon; Yu, I-Chen Ivorine; Yen, Jui-Hung Jimmy (Frontiers in Immunology, 2023)
Tissue plasminogen activator (tPA) is the only FDA-approved drug for the treatment of ischemic stroke. Delayed tPA administration is associated with increased risks of blood-brain barrier (BBB) disruption and hemorrhagic transformation. Studies have shown that interferon beta (IFNβ) or type I IFN receptor (IFNAR1) signaling confers protection against ischemic stroke in preclinical models. In addition, we have previously demonstrated that IFNβ can be co-administered with tPA to alleviate delayed tPA-induced adverse effects in ischemic stroke. In this study, we investigated the time limit of IFNβ treatment on the extension of tPA therapeutic window and assessed the effect of IFNβ on modulating microglia (MG) phenotypes in ischemic stroke with delayed tPA treatment. Mice were subjected to 40 minutes transient middle cerebral artery occlusion (MCAO) followed by delayed tPA treatment in the presence or absence of IFNβ at 3h, 4.5h or 6h post-reperfusion. In addition, mice with MG-specific IFNAR1 knockdown were generated to validate the effects of IFNβ on modulating MG phenotypes, ameliorating brain injury, and lessening BBB disruption in delayed tPA-treated MCAO mice. Our results showed that IFNβ extended tPA therapeutic window to 4.5h post-reperfusion in MCAO mice, and that was accompanied with attenuated brain injury and lessened BBB disruption. Mechanistically, our findings revealed that IFNβ modulated MG polarization, leading to the suppression of inflammatory MG but the promotion of ant-inflammatory MG, in delayed tPA-treated MCAO mice. Notably, these effects were abolished in MG-specific IFNAR1 knockdown MCAO mice. Furthermore, the protective effect of IFNβ on the amelioration of delayed tPA-exacerbated ischemic brain injury was also abolished in these mice. Finally, we identified that IFNβ-mediated modulation of MG phenotypes played a role in maintaining BBB integrity, because the knockdown of IFNAR1 in MG partly reversed the protective effect of IFNβ on lessening BBB disruption in delayed tPA-treated MCAO mice. Our study reveals a novel function of IFNβ in modulating MG phenotypes, and that may subsequently confer protection against delayed tPA-exacerbated brain injury in ischemic stroke.